﻿Nortriptyline overcomes corticosteroid resistance in NK and NKT-like cells from peripheral blood of patients with chronic obstructive pulmonary disease - Aliaksei G. Kadushkin; Anatoli D. Tahanovich; Lyudmila V. Movchan; Volha V. Dziadzichkina; Olga V. Levandovskaya; Tatsiana V. Shman (Belgorod National Research University, 2022)
Introduction: An antidepressant nortriptyline potentiates glucocorticoid (GC) action with synergistic suppression of inflammatory mediator release, but the precise molecular mechanism is unknown. Materials and methods: Peripheral blood cells from patients with chronic obstructive pulmonary disease (COPD) (n = 21) were incubated with nortriptyline (1 µM or 10 µM), budesonide (10 nM), or their combinations, followed by stimulation with phorbol myristate acetate (PMA) and ionomycin. Cytokine production, glucocorticoid receptor β (GRβ), histone deacetylase 2 (HDAC2) and histone H4 acetylation of K8 (HAT) expression, p65 NF-kB and p38 mitogen-activated protein kinase (p38 MAPK) phosphorylation in NK (CD3-CD56+) and NKT-like (CD3+CD56+) cells were analyzed by flow cytometry. Results: We observed that nortriptyline (10 µM) significantly attenuated the effects of PMA/ionomycin on the synthesis of interferon γ (IFNγ), interleukin 4 (IL-4), and IL-8, expression of GRβ and HAT, as well as p65 NF-kB and p38 MAPK phosphorylation in NK and NKT-like cells, whereas nortriptyline (1 µM) only inhibited IL-4 production by NK and NKT-like cells. Discussion: The combination of nortriptyline (10 µM) and budesonide decreased IFNγ, tumor necrosis factor α, IL-4, IL-8, and GRβ expression, as well as phosphorylated p38 MAPK and p65 NF-κB levels by NK and NKT-like cells above that of budesonide alone. Furthermore, the same association of drugs enhanced HDAC2 expression in NK and NKT-like cells. Conclusion: Collectively, our results show that nortriptyline might enhance GC function through modulation of HAT, HDAC2, GRβ, phospho-p38 MAPK expression. These data provide a strong rationale for combining nortriptyline with budesonide to treat COPD.